Effect of S‐1 on survival outcomes in 838 patients with advanced pancreatic cancer: A 7‐year multicenter observational cohort study in Taiwan - Hsiang‐Lan Lai; Yen‐Yang Chen; Chang‐Hsien Lu; Chia‐Yen Hung; Yung‐Chia Kuo; Jen‐Shi Chen; Hung‐Chih Hsu; Ping‐Tsung Chen; Pei‐Hung Chang; Yu‐Shin Hung; Wen‐Chi Chou (Cancer Medicine)
Abstract Objective Studies have rarely explored the efficacy of S‐1 in treating advanced pancreatic cancer outside Japan. This study compared the survival outcomes of patients with advanced pancreatic cancer treated with S‐1 with the survival outcomes of those without S‐1 treatment before and after S‐1 reimbursement was introduced in Taiwan in June of 2014. Method We retrospectively analyzed 838 patients with locally advanced or metastatic pancreatic cancer who underwent palliative chemotherapy from 2010 to 2016 at 4 institutes in Taiwan. For survival analysis, patients were categorized into two groups according to whether they received S‐1 treatment as palliative chemotherapy after diagnosis: (a) S‐1‐treated (n = 335) and (b) non‐S‐1‐treated (n = 503) groups. Results The median overall survival was longer in the S‐1‐treated group than in the non‐S‐1‐treated group (10.7 vs 6.0 mo, P < 0.001). Subgroup survival analyses showed that the S‐1‐treated group had more favorable outcomes than the non‐S‐1‐treated group in terms of stage III (19.6 vs 10.1 mo, P < 0.001) and stage IV (8.5 vs 5.3 mo, P < 0.001) disease. The disease control rates were 43.6% and 32.8% (P < 0.001) in patients treated with and without S‐1 in the first‐line setting, respectively. In multivariate analysis, exposure to S‐1 treatment was an independent prognosticator for survival. Conclusion Our results support the clinical use of S‐1 as the treatment of choice for patients with locally advanced or metastatic pancreatic cancer, particularly in resource‐limited situations.